PLASTIC WASTE PROCESSING BUSINESS PLAN - Kusuma Atmaja; Kusumo Bintoro (Sean Institute, 2023)
The development and density of population as well as changes in people's consumption patterns, especially in big cities, have resulted in increasingly diverse types and characteristics of waste. The data shows that plastic is the largest composition of inorganic waste that is disposed of at the Bantargebang final landfill (TPST) every day with 14.02% being plastic waste. According to the Minister of Industry, Agus Gumiwang Kartasasmita , the plastic recycling industry can produce a variety of value-added products with an economic potential of more than IDR 10 trillion per year and an export potential of US 141.9 million of recycled plastic derivative producbts. From this potential, the research results show that in 2 different scenarios, the plastic waste processing business plan has a positive NPV with a payback period of 1.78 years and 3.55 years respectively for the base and worst scenarios. These results indicate the feasibility of the plastic recycling business to run